2013
DOI: 10.1186/1471-2458-13-925
|View full text |Cite
|
Sign up to set email alerts
|

Trends in poverty risks among people with and without limiting-longstanding illness by employment status in Sweden, Denmark, and the United Kingdom during the current economic recession – a comparative study

Abstract: BackgroundPrevious studies have found higher employment rates and lower risk of relative poverty among people with chronic illness in the Nordic countries than in the rest of Europe. However, Nordic countries have not been immune to the general rise in poverty in many welfare states in recent decades. This study analysed the trends in poverty risks among a particularly vulnerable group in the labour market: people with limiting-longstanding illness (LLSI), examining the experience of those with and without emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 23 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…This has been noted in Sweden. 41 However, some Table 2. Changes in the proportion with low education and limiting longstanding illness in the study population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This has been noted in Sweden. 41 However, some Table 2. Changes in the proportion with low education and limiting longstanding illness in the study population.…”
Section: Discussionmentioning
confidence: 99%
“…This has been noted in Sweden. 41 However, some evidence suggests that a benefit system with a high level of adequacy, combined with effective ALMPs, can improve employment rates 49 rather than act as a disincentive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This variable is obtained from an item directed to all persons who report that they have a chronic/longstanding illness or condition: “Does this illness or disability (Do any of these illnesses or disabilities) limit your activities in any way?” Yes is coded 1 and no is coded 0. Some studies apply this item as a proxy of severe health impairments or chronic illness [ 23 , 28 , 29 ]. The intention of the item is to measure whether people are hampered in their usual activities by any ongoing physical or mental health problem, illness or disability [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is in particular serious mental and addiction disorders that tend to have these serious long-term social consequences. But even for a much larger group of people with different kinds of limiting illnesses it has, at least in Sweden, been found that the cuts in benefits and protection have increased the poverty rates in those groups (Falck et al, 2013).…”
Section: The Policy Entry Points To Tackle the Health Dividementioning
confidence: 99%